Evaluation of Blood Glucose Fluctuations in Diabetic Patients Receiving Corticosteroids - Malik, Rida; Batool, Rabia; Abdul Ur Rehman, Muhammad; Ali, Muhammad Mussadiq; Shakeel, Zunaira; Tarique, Huda (Indus Journal of Bioscience Research, 2025)
Background: Corticosteroids are widely used for treating various inflammatory and autoimmune conditions, but they are known to induce hyperglycemia, particularly in diabetic patients. Objective: The main objective of the study is to find the blood glucose fluctuations in diabetic patients receiving corticosteroids. Methods: A prospective observational study was conducted at Sheikh Zayed Teaching Hospital, Rahim Yar Khan, Pakistan, during August 2024 to January 2025. A total of 255 patients with pre-existing diabetes mellitus who received corticosteroid therapy were included in the study. Patients were monitored for blood glucose fluctuations using serial fasting, postprandial, and random glucose levels over 7 days. The primary outcomes included the mean daily glucose variation, frequency of hyperglycemia episodes (>250 mg/dL), and hypoglycemia (<70 mg/dL). Secondary outcomes included insulin dose adjustment frequency and requirement for additional antidiabetic therapy. Results: In 255 diabetic patients receiving corticosteroids, mean HbA1c was 8.2%, and fasting glucose was 145 mg/dL. Postprandial glucose peaked at 261 mg/dL by day 4. Glycemic variability increased, with glucose range rising from 58 to 83 mg/dL and MAGE from 47 to 68. Severe hyperglycemia (>250 mg/dL) occurred in 67.8%, and 17.2% had spikes >300 mg/dL. Treatment changes were needed in 31.7%, and 4.3% were hospitalized. High-dose steroids led to the greatest glucose elevations and variability. Conclusion: Corticosteroid therapy significantly worsens glycemic control in diabetic patients by inducing sharp fluctuations in blood glucose levels. Close monitoring and proactive management are essential to mitigate the risks of corticosteroid-induced hyperglycemia.